2012
DOI: 10.1155/2012/495218
|View full text |Cite
|
Sign up to set email alerts
|

Osteoconductivity and Hydrophilicity of TiO2Coatings on Ti Substrates Prepared by Different Oxidizing Processes

Abstract: Various techniques for forming TiO2 coatings on Ti have been investigated for the improvement of the osteoconductivity of Ti implants. However, it is not clear how the oxidizing process affects this osteoconductivity. In this study, TiO2 coatings were prepared using the following three processes: anodizing in 0.1 M H3PO4 or 0.1 M NaOH aqueous solution; thermal oxidation at 673 K for 2 h in air; and a two-step process of anodizing followed by thermal oxidation. The oxide coatings were evaluated using SEM, XRD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…To show the relationship between R B-I and WCA > 20 (deg. ), our previous in vivo results for TiO 2 -coated samples with Ra/μm < 0.1 are also plotted in the figure [11,13,14]. Each of the hydrothermally treated samples (WCA = 16 (deg.)…”
Section: In Vivo Testmentioning
confidence: 91%
See 1 more Smart Citation
“…To show the relationship between R B-I and WCA > 20 (deg. ), our previous in vivo results for TiO 2 -coated samples with Ra/μm < 0.1 are also plotted in the figure [11,13,14]. Each of the hydrothermally treated samples (WCA = 16 (deg.)…”
Section: In Vivo Testmentioning
confidence: 91%
“…An implant's osteoconductivity is usually influenced by its surface characteristics, because the formation of new bone on the implant is an interfacial reaction between the implant and body fluid. Therefore, it is important to modify the surface characteristics to improve the osteoconductivity of Ti, using, for example, hydroxyapatite coatings [1][2][3][4][5][6][7][8] or TiO 2 coatings [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, passive layers formed on the base of Ti6Al4V ELI alloy show good hydrophilous properties (wetting angle of about 63°). Studies carried out by other authors [43][44][45] showed that such surface layers ensure good osteoconductive properties of the implants.…”
Section: Resultsmentioning
confidence: 91%
“…Our previous in vivo results for TiO 2 -coated samples with Ra < 0.1 μm are also plotted in the figure [5,6]. Protein Adsorption Figure 5 shows the relationship between WCA and protein adsorption (peptide binding).…”
Section: Surface Characterizationmentioning
confidence: 87%
“…It is thought that the osteoconductivity of implants is usually influenced by surface substances. Several surface coating techniques, such as hydroxyapatite [1], TiO 2 [2][3][4][5][6], etc., have been researched to improve the osteoconductivity of the implant. This research has focused on the surface characteristics of implants or coating films, because the formation of new bone on the implant is an interfacial reaction between the implant and body fluid.…”
Section: Introductionmentioning
confidence: 99%